Growing up positive: adolescent HIV disclosure to sexual partners and others. Issue 12 (1st December 2020) - Kidman, Rachel; Violari, Avy
ABSTRACT: Over three million youth live with HIV worldwide. Very little is known about whether youth disclose their HIV status to family, friends or sexual partners, and what risks and benefits may accrue from doing so. This study characterizes HIV disclosure among 250 youth with perinatally-acquired HIV (PHIV; age 13–24 years) living in Soweto, South Africa. A third had self-disclosed their HIV status to at least one person; similarly, only a third of sexually-active PHIV had disclosed their HIV status to their most recent partner. It is not clear whether HIV disclosure alone leads to positive impact: we found perceived social support from the family was negatively associated with disclosure (aOR 0.81, 95% 0.70–0.94). PHIV who spoke to a provider about disclosure were more likely to share their HIV status with a sexual partner (aOR 2.48; 95% CI 1.28–4.81). However, those PHIV who disclosed their status were no more likely to use a condom. The World Health Organization recommends that health providers advise adolescent patients on safe disclosure, but we still lack evidence on the consequences for young people and effective tools to help them weigh benefits and risks.